Economic Report on Africa 2009 - United Nations (United Nations, 2009)
The Economic Report on Africa 2009 (ERA 2009) is organized into two parts. Part I examines global economic developments and their implication for Africa, analyses recent economic and social trends, and highlights emerging development challenges to the continent in 2008. Part II is devoted to the issue of regional value challenges to developing African agriculture. ERA 2009 then focuses on the question of how to enhance structural transformation of African agriculture through systematic efforts to develop regionally integrated value chains and markets for selected strategic food and agricultural commodities. Finally, the report urges African governments to operationalize commitments to develop agriculture, and suggests strategies that promote viable value chains at the national and regional levels.